2014
DOI: 10.1186/s12879-014-0606-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of West Nile virus infection in Nepal

Abstract: BackgroundAcute febrile illness is common among those seeking medical care and is frequently treated empirically with the underlying illness remaining undiagnosed in resource-poor countries. A febrile illness study was conducted 2009-2010 to identify known and unknown pathogens circulating in Nepal.MethodStudy methods included diagnostic testing and preliminary ELISA screening of acute and convalescent samples for diseases both known and unknown to be circulating in Nepal, including West Nile virus (WNV). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Lineage 2 WNV was sequenced from an acute febrile specimen collected in 2004 in Indonesia [ 81 ]. Recently, WNV has also been isolated from clinical specimens collected in Nepal from 2009-2010; sequenced fragments of both isolates showed homology primarily to lineage 1 viruses, but one fragment of each was more similar to lineage 2 than to lineage 1 [ 213 ].…”
Section: Wnv In Southern and Eastern Asia Australia And Oceaniamentioning
confidence: 99%
“…Lineage 2 WNV was sequenced from an acute febrile specimen collected in 2004 in Indonesia [ 81 ]. Recently, WNV has also been isolated from clinical specimens collected in Nepal from 2009-2010; sequenced fragments of both isolates showed homology primarily to lineage 1 viruses, but one fragment of each was more similar to lineage 2 than to lineage 1 [ 213 ].…”
Section: Wnv In Southern and Eastern Asia Australia And Oceaniamentioning
confidence: 99%
“…The public health is highly affected by the Chikungynya, Dengue, JE, and West Nile Fever in the country (Rutvisuttinunt et al 2014). Chikungunya is caused by an icosahedral positive-sense ssRNA virus called Chikungunya virus (CHIKV) that falls in Alphavirus genus within Togaviridae family.…”
Section: Vector-borne Viral Diseasesmentioning
confidence: 99%
“…Another vector-borne disease in Nepal is the West Nile Fever (WNF) caused by positive-sense ssRNA virus that belongs to the genus Flavivirus within the family Flaviviridae (Rutvisuttinunt et al 2014). WNF possesses 8 different lineages with 2 main virulent lineages (Lineage 1 with clades 1a, 1b, and 1c and Lineage 2) responsible for outbreaks in humans, the clade 1b containing Kunjin virus has already been reported to infect 3% pigs in Nepal (Pant et al 2006) suggesting existing risks of zoonosis in future.…”
Section: Vector-borne Viral Diseasesmentioning
confidence: 99%
“…Other emerging viral infections: Very recently, in 2014, first case of chikungunya (transmitted by Aedes mosquito) has also been found in Nepal [103,104]. Serological study among patients presenting with fever has shown seropositive rate of 3.6% [105]. A case of chikungunya has been found even in Kathmandu Valley.…”
Section: Emerging Infectionsmentioning
confidence: 99%